الفكر التداولي عند ابن خلدون وعلاقته بتعليمية اللغات - ميسة, محمد الصغير (جامعة الوادي - University of Eloued, 2017)
تناولت من خلال هذا المقال موضوع الفكر التداولي عند ابن خلدون وعلاقته بتعليمية اللغات، حيث بينت فيه العلاقة بين التداولية الغربية وتعريف اللغة عند ابن خلدون، وركزت على النقاط المشتركة بينهما، والمتمثلة في القصدية، والأفعال الكلامية، والإبانة. صنف ابن خلدون علوم اللسان إلى: نحو،أدب، لغة وبيان، وقدّم النحو على بقية الأنواع؛ لأن به يتم الإفصاح عن أغراض المتكلمين. لقد خاض ابن خلدون أغوار العملية التعليمية، وركز على أهم عناصرها: المعلم والمتعلم والمعرفة، وفي تناوله لهذه المسألة صلة وثيقة بالتداولية التي تحرص على تحقيق التواصل الفعّال بين المرسل والمرسل إليه In my article, I dealt with pragmatism and its relationship with the language teaching according to Ibn Khaldoun, then I defined it according to the Western scientists and Arabic Dictionaries. I focused much on the shared points between them that are , actions spoken , the intentionality and designation. Ibn Khaldoun classifies linguistics into ;grammar , language , literature and statement. He gives much more importance to grammar , because the role of grammar is to decipher the objectives of the speakers rather than syntax expressions. Ibn Kaldoun went deeper exploring the teaching process, concentrating on its most important factors which are , the teacher , the learner and the knowledge . Here lies the link between these factors and pragmatism that focuses much on realizing the effective contact between the addresser and the recipient. At the end Ibn Kaldoun clarifies that the language skill could only be acquired by listening , memorization and use . All in all , language could be acquired effectively by having a linguistic bath.
مقال
Keywords: الفكر التداولي ؛ابن خلدون ؛علاقته ؛ تعليمية اللغات